KUKIS IKAN MUJAIR DAN DAUN KELOR SEBAGAI MAKANAN PENDAMPING ASI KAYA PROTEIN - Hidayanti, Lilik; Rosa, Mila; Susilawati, Prima Endang (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Babies over 6 months of age need complementary foods with high protein content. Tilapia fish and Moringa leaves have a high protein content, so they can be used as food to food fortification in making cookies. The aim of this research is to analyze the acceptability and protein content of cookies fortified with tilapia fish meal and moringa leaf flour. The research design used was Research and Development (R&D) with a Completely Randomized Design (CRD), using four treatments and two replications. The selected formula is determined based on the average value of acceptability of color, aroma, taste and texture. Analysis of protein content using the Kjeldahl method. There was a difference in the acceptability (preference for color, aroma, taste and texture) of cookies fortified with tilapia fish meal and moringa leaf flour compared to the control formula. The selected formula based on the average value of color, aroma, taste and texture was formula F3 (87g wheat flour, 6g tilapia fish meal and 2g moringa leaf flour). The selected formula, namely formula F3, contains protein per 100g, 2.85g higher than the control formula (F0). It is necessary to analyze macronutrients and other micronutrients so that the entire nutritional content of cookies can be known